The real effects of bank-driven termination of relationships: Evidence from loan-level matched data - Nakashima, Kiyotaka; Takahashi, Koji (Journal of Financial Stability, 2018)
In this study we use a matched dataset of Japanese banks and firms to examine how bank-driven terminations of bank-borrower relationships affect the investments of the borrowers. We find that bank-driven terminations significantly decrease investment, exerting an effect that exceeds that due to credit reductions within continuing relationships. Our results also show that the unwanted effect of bank-driven terminations grows as the loan market deteriorates as a whole, which prevents firms from obtaining funding from other sources after their relationships with banks are terminated. Our findings coincide with previous literature emphasizing financial frictions in the matching process and the importance of relation-specific assets in credit markets.